Implementasi Pendidikan Karakter Melalui Program Tahfidz di SD Islam Al-Azhar 29 Semarang - Azka, Maulida Fikrotul; Nurharini, Atip; Nurrizky, Awalinda Ika; Yuserna, Djenar Mahesa Ayu; Rahmawati, Ely Eka; Kumalasari, Cahyani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character education is an effort made by educators to help students develop good behavior. Therefore, to help students develop character at school, educators and curriculum components-which include teaching and learning activities and extracurricular activities-must collaborate. Descriptive qualitative research was used in this study. Interview, observation, and documentation were the methods used in data collection. To verify the accuracy of the data, researchers used source triangulation and procedure triangulation. The research findings show that the character education method of the Qur'an memorization program at Al-Azhar 29 Semarang Islamic Elementary School is by way of: Before reading and memorizing the Qur'an, students must: a) purify from hadats (wudhu); habits like this give birth to a clean character; b) develop a disciplined character by getting used to reading and memorizing the Qur'an before studying. c) Teachers get used to students reading and memorizing the Qur'an before studying; d) students must deposit at least 12 verses every week in order to reach the memorization target that has been set. d) The quality of honesty is born from the habit of reading and memorizing the Qur'an.